2007
DOI: 10.1007/s00464-007-9480-9
|View full text |Cite
|
Sign up to set email alerts
|

Midline versus nonmidline laparoscopic incisional hernioplasty: a comparative study

Abstract: Laparoscopic incisional hernioplasty can be applied to nonmidline defects with the same rates of morbidity and recurrence as for patients with midline defects. The four types of nonmidline defects seem to have their own evolutionary characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…In parallel, the recent development of laparoscopic incisional hernia repair with encouraging results has added another alternative in the choice of surgical approach [9]. Compared with the laparoscopic approach for the treatment of LIH, Moreno-Egea et al [9] reported in a cohort of 53 patients an average operative time of 60 min, while it was 136 min in our study. However, 31 % of our patients had miltifocal defects versus 9 % for Moreno-Egea et al [9].…”
Section: Discussionsupporting
confidence: 51%
“…In parallel, the recent development of laparoscopic incisional hernia repair with encouraging results has added another alternative in the choice of surgical approach [9]. Compared with the laparoscopic approach for the treatment of LIH, Moreno-Egea et al [9] reported in a cohort of 53 patients an average operative time of 60 min, while it was 136 min in our study. However, 31 % of our patients had miltifocal defects versus 9 % for Moreno-Egea et al [9].…”
Section: Discussionsupporting
confidence: 51%
“…A multicenter clinical trial showed that seroma rate is twofold in laparoscopic repair [188]. Other large trial reported contradictory data with higher seroma rates after open surgery [189].…”
Section: Seroma and Hematomamentioning
confidence: 99%
“…In our study, specialization in the treatment of abdominal wall hernias and the multidisciplinary approach helps to explain the size of the study [15].…”
Section: Discussionmentioning
confidence: 95%